KATA PENYUKAT TRADISIONAL DALAM BAHASA DAYAK KANAYATN - Ana, Meiliana Vena; Madeten, Sesilya Saman; Syahrani, Agus (Universitas Tanjungpura, 2022)
This study aims to find out objectively about the traditional word in the Dayak Kanayatn language. The problems of this research are the inventory of traditional penlight words in the Dayak Kanayatn language, the form and lexical meaning of the traditional penlight words in the Dayak Kanayatn language, and the implementation of learning the results of the traditional penlight word research into Indonesian language learning in schools. This research uses descriptive method in the form of qualitative. Data collection techniques, namely, observation techniques, interview techniques, and note-taking techniques. This research resulted in 52 data of traditional blocking words in the Pakumbang Village community, which were divided into five traditional blocking words which favored living plant objects, 23 traditional blocking words which favored solid inanimate objects, 10 traditional dissolving words to love liquid inanimate objects, 10 traditional blocking words using inanimate objects. Human external organs, and 4 traditional barrier words to love distance conditions. There were also 50 inventory words of traditional cursing words in the form of one morpheme (monomorphemic) and 2 traditional cursing words in the form of two or more morphemes (poly morphemic). The meaning contained in the inventory of traditional words in the Dayak Kanayatn language is based on lexical meaning. The form of the Indonesian language learning text contained in it using the word